Blended Learning in Engineering Mathematics Classrooms: Case Study on the Electrical Engineering Department Polytechnic of Semarang - Iswanti Ciptowiyono (International Conference on Industrial Revolution for Polytechnic Education, 2019)
In this paper, we describe the blended learning in Engineering Mathematics classroom. The term blended here refers to the use of technology (i.e. online resources, videos, applications, software) as part of teaching and learning activities. The participants are fifty D4 (four-year-diploma) engineering students, 78% male and 22% female with age between 18 – 21 years old. This two-week observation use an instrument consist of two set questions on the application of matrix and determinant to determine the electrical current in both direct current (DC) and alternating current (AC) networks and the learning style was set collaboratively in small groups of five students. The results show as the introduction of the study students collect online learning resources (E-books), watch videos related to the topic, and take the online quiz (Google Form based quiz); as the core part of the study students use Matrix Calculator (Android based application) to calculate the determinants, scientific calculator to finalize the answer and Power Point (software by Microsoft) to present their works and as the final part of the study students use Whatsapp (Android based chat application) to submit their report and receive feedback.